Investigation of the accuracy and roughness in the laser powder bed fusion process. Issue 2 (3rd April 2018) - Calignano, F.
ABSTRACT: Laser powder bed fusion (L-PBF) process has had a rapid growth in the industrial fields because of the capability to manufacture metallic complex shapes. The purpose of this study is to investigate the accuracy and surface roughness of parts manufactured by L-PBF in the AlSi10Mg alloy. The results showed that the choice of parameters of conversion from the CAD model to STL file and the setting of process parameters can affect the accuracy. In the L-PBF process, the staircase effect, inherent in additive manufacturing technologies due to the layered nature of the process, is not visible due to the melting of thin layers of metal powder. The surface roughness is mainly caused by the process parameters, orientation and position of the part with respect to the recoating blade and by the presence of partially fused particles that adhere to the molten part.